SITUS CANDI SAMBISARI YANG PERNAH TERPENDAM - Masyhudi (Berkala Arkeologi, 2005)
Geomorphologically, Sambisari Temple site is located on the alluvial plain at the foot of Mount Merapi, so that the land is fertile, it is easy to get water and the land is suitable for living and farming. This reason is very possible for the construction of temples. However, because then the area where the site was covered by volcanic ash as a result of the eruption of Mount Merapi which was very powerful due to the combination of the three tectonic, gravitational and volcanic forces that caused the volcanic cone of Merapi to flow sunken hyperbolic faults. This results in the level of soil fertility around the Sambisari Temple Site decreasing and even becoming damaged, because based on the soil material the sediment comes from the main material of lava deposits and fluvial deposits resulting from cleavage of pyroclastic materials from the eruption of Merapi Volcano in the form of boulder, gravel, sand, and dust. While the development of the soil around the Sambisari Site is still in the initial stage which is a type of horizon regosol soil and this soil has not experienced horizon differentiation, so that the soil profile is homogeneous. Such soil properties can be observed through the texture of dusty sand to gravel dust.